Volatility Transmission and Risk Spillover Effects Between Oil and Stock Sector Markets in Malaysia : An Implication for Portfolio Management - Tan, Bee Ngor (2016)
This paper examines the volatility and risk spillover effects between oil and stock sector markets in Malaysia and also analyzes the dynamics interrelationship of oil and stock returns for the implications of portfolio management. As different from previous studies, this paper investigates total eleven stock sector markets which provide useful insight for portfolio diversification and risk hedging. The study of volatility spillover effects involved a whole sample period of ten years and a separate sub-period analysis for Oil Crisis 2014 to identify any change in dynamics as a result of oil demand shocks. VAR-GARCH is the benchmark model to study the volatility spillover effects, another two MGARCH models CCC-GARCH and BEKK-GARCH are included to compare the results for portfolio simulation and hedging effectiveness. The findings suggest that in Malaysia, there is spillover effect present in both markets with strong positive impacts discovered in financial sector, other sectors generally show diminishing spillover effects from oil shocks. The portfolio simulations suggest a larger holding of stock than oil asset in an optimal portfolio. Oil asset could be used as a hedging tool to minimize risk and also to improve overall risk-adjusted returns. The findings of the study provide important implications for making sound economics policies, volatility forecasting and stock valuation, risk hedging and portfolio diversification. There is robustness checking in place for the estimates, however, this research is subject to limitations which could be improved by future study.